Qualidade de vida no trabalho de docentes e técnico administrativos das Universidades Federais de Ensino Superior: revisão integrativa - Carneiro, Maria Tereza Divalda (2024)
The Quality of Work Life (QWL) refers to factors related to mobilization, social commitment, and concern for the well-being of workers in the performance of their duties, aiming to achieve professional effectiveness. In the Brazilian university context, it has been observed that, in recent years, there has been a significant increase in investments in federal public higher education. There is, undoubtedly, a close relationship between the dynamics of the economy and the development of higher education, which, consequently, correlates with the growing interest in QWL regarding the job satisfaction of employees. In this sense, there is a recognized need for studies focused on measuring the QWL of employees assigned to Higher Education Institutions (HEIs). In recent years, QWL has gained increasing importance and relevance, as the activities carried out by both technical-administrative staff and faculty members contribute to and influence the quality of services provided to the academic community and the external public. The objective of this research is to analyze the Quality of Work Life (QWL) of Faculty and Technical-Administrative Staff in Federal Public Higher Education, based on scientific publications from 2012 to 2022. This analysis is guided by theoretical-methodological approaches and the discussions established, according to a qualitative Integrative Literature Review (ILR). The results suggest that, overall, the perception of QWL among technicaladministrative staff is more satisfactory than that of faculty members. However, an examination of the sample used in the studies reveals that it is insufficient to conduct a comprehensive and in-depth analysis of the studied Higher Education Institutions, as the studies were applied to small groups or specific sectors within the institutions. Therefore, it is concluded that there is a need to continue and expand research in the studied institutions, preferably using a quantitativequalitative methodological approach, to obtain greater validity and reliability in the results. Furthermore, it is recommended to incorporate new evaluation instruments and external indicators in the research analysis to positively impact the investigation outcomes. Additionally, it is suggested that Higher Education Institutions invest in QWL Programs aimed at prioritizing effective work organization, preventing work overload, and fostering a more humanized work environment, thereby improving the quality of life of their employees.